Sugar–Protein Connectivity Impacts on the Immunogenicity of Site‐Selective Salmonella O‐Antigen Glycoconjugate Vaccines. (9th September 2015) - Stefanetti, Giuseppe; Hu, Qi‐Ying; Usera, Aimee; Robinson, Zack; Allan, Martin; Singh, Alok; Imase, Hidetomo; Cobb, Jennifer; Zhai, Huili; Quinn, Douglas; Lei, Ming; Saul, Allan; et al.
Abstract: A series of glycoconjugates with defined connectivity were synthesized to investigate the impact of coupling Salmonella typhimurium O‐antigen to different amino acids of CRM197 protein carrier. In particular, two novel methods for site‐selective glycan conjugation were developed to obtain conjugates with single attachment site on the protein, based on chemical modification of a disulfide bond and pH‐controlled transglutaminase‐catalyzed modification of lysine, respectively. Importantly, conjugation at the C186‐201 bond resulted in significantly higher anti O‐antigen bactericidal antibody titers than coupling to K37/39, and in comparable titers to conjugates bearing a larger number of saccharides. This study demonstrates that the conjugation site plays a role in determining the immunogenicity in mice and one single attachment point may be sufficient to induce high levels of bactericidal antibodies.